2015
DOI: 10.1002/mma.3800
|View full text |Cite
|
Sign up to set email alerts
|

Effective thermal conductivity of inhomogeneous medium containing gas‐filled inclusions

Abstract: Communicated by W. SprößigDetermination of effective physical parameters of gas-filled porous media is of practical interest to a wide spectrum of applications from construction industry to petrophysics. The classical equations of thermal conductivity are not applicable for sufficiently small pores, the characteristic size of which is comparable with the mean free path of gas molecules. In this case, for description of the gas behavior, it is necessary to use the methods of physical kinetics and rarefied gas d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…One defines the total volume of intra oolitic pores Ω o = Ω a + Ω s o (24) and the porosity of the oolite phase at the mesoscopic scale…”
Section: Volume Fractions and Constituentsmentioning
confidence: 99%
See 1 more Smart Citation
“…One defines the total volume of intra oolitic pores Ω o = Ω a + Ω s o (24) and the porosity of the oolite phase at the mesoscopic scale…”
Section: Volume Fractions and Constituentsmentioning
confidence: 99%
“…A detailed review of thermal conductivity data sets for geomaterials made of natural soil particles, crushed rock particles and sedimentary rock including analysis of influence of particle shape, grains pore-size distributions, fluid saturated (air and liquid water) is given in [23]. It may be noticed that [24] have recently studied thermal conductivity of gas saturated porous materials taking into account methods of statistical physics and rarefied gas dynamics. They have shown that in the slip flow regime corresponding to low Knudsen number, it is necessary to use the method of rarefied gas dynamics to correctly predict the effective thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%